How does greenwashing affect green word of mouth through green skepticism? Empirical research for fast fashion Business - Rika Promalessy; Tanti Handriana (Cogent Business & Management, 2024)
This study aims to examine the direct and indirect effects of greenwashing on negative green word of mouth, with green skepticism as a mediator, in the fast fashion industry in Indonesia. This study is quantitative in nature, with data being collected using a survey. The non-probability, purposive sampling method was employed with criteria including respondents being of Generation Z, currently aged 17 to 28 years, and aware of fast fashion companies. A total sample size of 397 was utilized, and analysis was conducted using partial least squares structural equation modeling. The results suggested that greenwashing significantly positively affects green skepticism and negative green word of mouth. Green skepticism has a significant positive effect on negative green word of mouth. Furthermore, green skepticism mediates the effect of greenwashing on green word of mouth. To the authors' knowledge, this study extends the literature that discusses the effect of greenwashing on negative green word of mouth through green skepticism. This research provides a new perspective, especially on the stimulus-organism-response theory seen from negative antecedents, which is rarely discussed in developing countries. This research will provide useful information for companies to avoid greenwashing practices in promoting sustainability. For the government, issuing consumer protection laws regarding greenwashing rules is suggested. This study has several limitations, including that it was only conducted in Indonesia. Therefore, future research can be developed involving other countries for comparison.
Keywords: 650; Greenwashing; green skepticism; green word of mouth; stimulus organism response